The impact of live streamers’ social capital on viewers’ purchase intention - Hong, Kai Song (2022)
In 2020, the Covid-19 pandemic causes dramatic shifts in almost all industries, most notably the internet realm. Fewer people visit the business in person because they are urged to shop online instead. Customers are distancing themselves from traditional brick-and-mortar establishments. Because of this reality, most companies are shifting their focus to live streaming. Live streaming allows for two-way communication between the live streamers and the viewers, which improves the viewers knowledge of the product and boost viewers purchase intention. Why do viewers put their faith in anonymous and unproven live streamers from internet? This study examined the impact of live streamers' social capital on viewers' purchase intention in order to better understand this phenomena. The results demonstrated that the the live streamer's social capital which professionalism, trust and reciprocity all contributed to in the viewer's purchase intention.